2017
DOI: 10.1080/14764172.2017.1376099
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted hair removal for facial hirsutism in women: A review of evidence

Abstract: Poly cystic ovarian syndrome (PCOS) has been described as the common diagnosis for hirsutism in women. Facial hirsutism is by far the most distressing symptom of hyperandrogenism in women with PCOS. A statistically significant improvement in psychological well-being has been reported in patients with PCOS allocated for laser-assisted hair removal. The theory of selective photothermolysis has revolutionized laser hair removal in that it is effective and safe, when operated by sufficiently trained and experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The effectiveness of hair removal with the long‐pulsed 755 nm alexandrite laser was first described by Finkel et al 13 Since then, many studies have confirmed the efficacy and safety profile of this device, 14‐17 with a median hair reduction rate of 70% to 96% 8,10 . According to literature data, our patients showed an average hair reduction of 87% after SP Motus AX treatment and 78.5% after Moveo.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The effectiveness of hair removal with the long‐pulsed 755 nm alexandrite laser was first described by Finkel et al 13 Since then, many studies have confirmed the efficacy and safety profile of this device, 14‐17 with a median hair reduction rate of 70% to 96% 8,10 . According to literature data, our patients showed an average hair reduction of 87% after SP Motus AX treatment and 78.5% after Moveo.…”
Section: Discussionsupporting
confidence: 58%
“…The effectiveness of hair removal with the long-pulsed 755 nm alexandrite laser was first described by Finkel et al 13 Since then, many studies have confirmed the efficacy and safety profile of this device, [14][15][16][17] with a median hair reduction rate of 70% to 96%. 8,10 According to literature data, our patients showed an average hair reduction of 87% In a prospective study by Garcia et al 19 In the literature, many uncommon alexandrite side effects have been reported, including purpura, 24 Interestingly, our study showed a significant improvement of PFC in all our patients.…”
Section: Discussionmentioning
confidence: 99%
“… The unreasonable use of laser methods as monotherapy, which do not have a sufficient reliable evidence base, are not included in modern treatment guidelines and have auxiliary value in the complex therapy of the pathology being treated (eg, acne, inflammatory rosacea, hirsutism 18 ). Clinical case: An increase in the severity of the inflammatory process in a 22‐year‐old patient with conglobate acne after 2 sessions of laser treatment using a laser without prescribing systemic and topical drug therapy (Figure 2A).…”
Section: Etiological Classification Of Laser Complicationsmentioning
confidence: 99%
“…The unreasonable use of laser methods as monotherapy, which do not have a sufficient reliable evidence base, are not included in modern treatment guidelines and have auxiliary value in the complex therapy of the pathology being treated (eg, acne, inflammatory rosacea, hirsutism 18 ).…”
Section: Etiological Classification Of Laser Complicationsmentioning
confidence: 99%
“…8-10 Nowadays, laser-assisted hair removal (LAHR) is the most common procedure, currently approved to treat this disorder. 11 Although previous studies have shown a desirable effect of LAHR on hirsute females' quality of life through the assessment of DLQI, 10,12,13 they mainly used the visual analogue scale to evaluate the effect of LAHR on the severity of hirsutism and omitted the evaluation of depression as a majorrelated psychological problem. The goal of the current study was to assess how LAHR affected the quality of life, depression severity, and the Ferriman-Gallwey score which measures how severe hirsutism is.…”
Section: Introductionmentioning
confidence: 99%